Nuclear Ca2+ signalling in arbuscular mycorrhizal and actinorhizal endosymbioses: on the trail of novel underground signals. Issue 2 (5th December 2016) - Barker, David G.; Chabaud, Mireille; Russo, Guilia; Genre, Andrea
Summary: Root endosymbioses are beneficial associations formed between terrestrial plants and either bacterial or fungal micro‐organisms. A common feature of these intracellular symbioses is the requirement for mutual recognition between the two partners before host‐regulated microbial entry. As part of this molecular dialogue, symbiosis‐specific microbial factors set in motion a highly conserved plant signal transduction pathway, of which a central component is the activation of sustained nuclear Ca 2+ oscillations in target cells of the host epidermis. Here, we focus on recent findings concerning this crucial Ca 2+ ‐dependent signalling step for endosymbiotic associations involving either arbuscular mycorrhizal fungi or nitrogen‐fixing Frankia actinomycetes, and in particular how this knowledge is contributing to the identification of the respective microbial factors. Contents Summary 533 I. Introduction 533 II. Nuclear calcium reporters illuminate the path to AM fungal signalling 534 III. Ca 2+ signalling at the heart of the Frankia /actinorhizal host dialogue 536 IV. Conclusions and future outlook 536 Acknowledgements 537 References 537